Creative Media City: The Indicators for Youth Development - Pratumsuwan, Kesinee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
A creative media city refers to a local community where all groups of people have opportunities to access good media and space, gain media literacy and can develop their own wisdom. This research objective was to develop a creative media city conceptual framework and indicators. It was researched from relevant documents, focus group discussions and in-depth interviews with key informants comprising academics, developers, community leaders and juveniles in three prototype provinces: Mae Hong Son, Surin and Phetchaburi. From the study it was found that a creative media city should hold to three good principles; good media, good space and good wisdom. As a matter of fact, good media can be like a virtual ‘upstream water’ source that consequently produces a good design and management process of space that results in a “good space” that can be compared to the ‘middle stream.’ And finally, both good media and good space can generate wise people who act as the immunity at the ‘downstream’ section. And vice versa, the intellectual people and community with good immunity can further create innovation that results in cyclic “good media” and “good space”. The main indicator components include activity, environment and result components. The implementation of a community driven to be a creative media city requires cooperation of various principal institutes in the community. The final outcome is that people in the community can change and be enlightened. They are aroused to modify their own behaviors despite communication, consumption and social behaviors.